2010
DOI: 10.1186/1471-2180-10-160
|View full text |Cite
|
Sign up to set email alerts
|

Fibronectin-binding protein B variation in Staphylococcus aureus

Abstract: BackgroundFibronectin binding proteins A and B (FnBPA and FnBPB) mediate adhesion of S. aureus to fibrinogen, elastin and fibronectin. We previously identified seven different isotypes of FnBPA based on divergence in the fibrinogen- and elastin-binding A domains. The variation created differences in antigenicity while ligand binding functions were retained. Here, FnBPB variation was examined in both human and bovine isolates and compared to that of FnBPA.ResultsSeven different fnbB allelic variants were identi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

5
70
0
1

Year Published

2011
2011
2024
2024

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 61 publications
(76 citation statements)
references
References 38 publications
5
70
0
1
Order By: Relevance
“…9). The K D for the interaction was 0.532 Ϯ 0.028 M, an affinity that is nearly 4-fold higher than the interaction between FnBPB and FBG (33).…”
Section: Measurement Of the Dissociation Constant Of Fnbpb Binding Tomentioning
confidence: 87%
See 2 more Smart Citations
“…9). The K D for the interaction was 0.532 Ϯ 0.028 M, an affinity that is nearly 4-fold higher than the interaction between FnBPB and FBG (33).…”
Section: Measurement Of the Dissociation Constant Of Fnbpb Binding Tomentioning
confidence: 87%
“…There are seven isoforms of FnBPB N2N3 subdomains with amino acid sequence identities ranging from 61 to 85% (33). FnBPBs from strains 8325-4, LAC, and BH1CC have identical amino acid sequences and belong to isoform I.…”
Section: Measurement Of the Dissociation Constant Of Fnbpb Binding Tomentioning
confidence: 99%
See 1 more Smart Citation
“…The sequences of the fnbA and fnbB genes of HA-MRSA strain BH1CC (CC8) were determined by DNA sequencing of PCR products amplified from genomic DNA. BH1CC expresses fibronectin binding proteins with A domain amino acid sequences identical to those of FnBPA and FnBPB from strain 8325 (isotype I) (20,21). Ligand affinity blotting analysis of proteins solubilized from the cell wall and probed with biotinylated fibronectin revealed that FnBPs were expressed at much higher levels by BH1CC than by laboratory strain SH1000 in the exponential phase of growth ( Fig.…”
Section: Expression Of Fibronectin Binding Proteins By S Aureus Bh1ccmentioning
confidence: 96%
“…The N2 and N3 subdomains of FnBPA and FnBPB have undergone considerable amino acid sequence divergence. At least seven different isotypes of FnBPA and FnBPB exist, and all bind to ligands with similar affinities despite considerable antigenic differences (20,21).…”
mentioning
confidence: 99%